Building upon the Foundation: Mentoring and Service in the Applied Sport Management Association - Jeffrey C Petersen (Journal of Applied Sports Management, 2023)
The Applied Sport Management Association’s Distinguished Service & Mentorship Award was initiated in 2022 as a renaming and repurposing of the ASMA Scholar Lifetime Achievement Award presented from 2009 to 2020. This service and mentorship award recognizes an ASMA member who has exhibited continued, exemplary service to ASMA, who connects sport management research with practitioners in an applied manner, and who demonstrates dedication to students and mentorship within the ASMA. Recipients of this award provide a keynote address to the ASMA membership at the annual conference. The content of this address is published in the Journal of Applied Sport Management, the peer-reviewed journal and official publication of ASMA.
Keywords: mentorship; service; facilities